Diversity of fish caught by fishermen at Warido Amberimasi village: Development of supplement book for animal diversity course - Rumbruren, Yakolina; Damopolii, Insar; Nebore, Idola Dian Yoku (Univeritas Papua, 2022)
This study aimed to analyze the validity and student responses to the supplement book developed in the animal diversity course based on the identification of fish species caught by fishermen in Warido Amberimasi Village, Biak Numfor Regency. This development research refers to the ADDIE development model; this study is limited to ADD stage. Research subjects include 4th-semester biology education students at the University of Papua. The object of research is a complementary book. The instruments used to assess the validity and practicality of teaching materials include a validity assessment sheet by expert validator one and a validity assessment sheet by expert validator two. Based on the validity of the supplement book with validity criteria with a percentage value of 81.82% (very valid) and the results of student responses to supplement books with an average response value of 86.80% included in the very good category, the supplement book developed can be used as a reference in the student learning process Biology education for 4th-semester students at the University of Papua.